Production of English Diphthongs: A Speech Study - Putri Ayu Dosia; Akhyar Rido (Universitas Teknokrat Indonesia, 2017)
In the 21th century, English is a key of all elements in education, politics, economy and international trade. English is even used in most of International events. This study aimed at analysing the official speech of Mr. Joko Widodo known as Jokowi, the seventh President of Republic of Indonesia, in APEC forum 2014 in China, focusing on the production of diphthongs. The researchers used conceptual framework of Roach that divides diphthong into two types; first, closing diphthong such as /eɪ/, /aɪ/, /ɔɪ/,/әʊ/,/aʊ/ and second, centring diphthong like /ɪә/, /eә/,/ʊә/. This study employed qualitative method while the data were collected through library research. This study found 71 data of English diphthong. Diphthong /eɪ/ was produced 21 times, diphthong /aɪ/ was used 15 times, diphthong /ɔɪ/ was mentioned once, diphthong /aʊ/ was stated 7 times, diphthong /әʊ/ was produced 16 times, diphthong /ɪә/ used 6 times, diphthong /eә/ was mentioned 3 times, and diphthong /ʊә/ was stated twice. In other words, this study showed that Mr. Jokowi could produce the diphthong sounds that matched the Oxford Advanced Learner’s Dictionary. However, this study also found that he faced challenges in producing many diphthong sounds by frequently producing diphthongs sounds as pure vowels.